ナンキョクサン ビサイ ソウルイ ノ バイヨウ 1 ニシ オングルトウ カラ ブンリ シタ ナンキョク トクサンシュ ノ ケイソウ NAVICULA MUTICOPSIS VAN HEUPCK - 綿貫, 知彦; ワタヌキ, トモヒコ; 唐沢, 栄; カラサワ, サカエ; WATANUKI, Tomohiko; KARASAWA, Sakae (国立極地研究所, 1975)
P(論文) Antarctic endemic diatom Navicula muticopsis van HEURCK var. muticopsis f. muticopsis was isolated from samples of fresh lakes, ponds and pools at West Ongul Island, Antarctica during the period from 11 January to 4 February 1974. Cultured strains have been preserved at Kanagawa Prefectural Public Health Laboratories. departmental bulletin paper